Incomes Policies, Expectations and the NAIRU - Wolfgang Pollan (Austrian Institute of Economic Research (WIFO), 2006)
Since the 1960s, several countries have adopted incomes policies to control inflation that was interpreted as the result of a distributional struggle between business and labour unions. This theoretical framework, termed the "battle of the mark-ups", has also formed the basis for estimating expectations-augmented Phillips curves and calculating the NAIRU. Nonetheless, the effects of incomes policies on inflation have been neglected in recent writings on the natural rate of unemployment. It is paradoxical that the literature on the NAIRU, an economic indicator that has been developed explicitly to guide economic policy, ignores past policy interventions. This criticism can be expanded to encompass any kind of policy measures that affect the labour market and the wage and price setting system. Disregard of these policy measures in the estimation of the natural rate of unemployment will yield biased estimates of this variable and its relation to unemployment. These points have been elaborated for the Austrian economy, which has been characterised by a strong degree of policy interference in the operation of the labour market as well as in the wage and price setting system, but apply equally well to other European economies.
Keywords: 330; Natürliche Arbeitslosenquote; Phillips-Kurve; Schätzung; Arbeitsmarktpolitik; Wirtschaftspolitik; Österreich